Archetypes of blockchain-based business models in enterprise networks - Alexander Grünewald; Tan Gürpinar; Carina Culotta; Alicia Guderian (Information Systems and e-Business Management, 2024)
Abstract Many enterprises are currently engaged in developing blockchain-based business models. Enterprise networks offer a variety of potential applications for blockchain solutions as they benefit from transparency and security as well as automation of handling~data, material, and financial flows along their supply chains. Despite profound potentials, the indicated business models are still in their early stages and need further investigation. To provide an overview of existing blockchain-based business models in the context of enterprise networks, the underlying paper designs a multidimensional taxonomy and identifies several archetypes of blockchain-based businesses. For the taxonomy development, data from 101 blockchain start-ups serves as a basis for empirical validation. Using hierarchical clustering and the k-means method, seven archetypes that sharpen the understanding of how blockchain solutions affect business models in enterprise networks and enable new business models are derived. The proposed work results~are intended to be applied in future research and practice to classify and~assess the integration of blockchain solutions into existing business models and to support developing new ones that leverage emerging technological capabilities.
Keywords: 330; Blockchain technology; Business models; Enterprise networks; Taxonomy; Archetypes